One Solution for All: Searching for Universal Aptamers for Constantly Mutating Spike Proteins of SARS‐CoV‐2. (31st May 2022) - Li, Jiuxing; Zhang, Zijie; Amini, Ryan; Li, Yingfu
Abstract: Aptamers that can recognize the spike (S) protein of SARS‐CoV‐2 with high affinity and specificity are useful molecules towards the development of diagnostics and therapeutics to fight COVID‐19. However, this S protein is constantly mutating, producing variants of concern (VoCs) that can significantly weaken the binding by aptamers initially engineered to recognize the S protein of the wildtype virus or a specific VoC. One strategy to overcome this problem is to develop universal aptamers that are insensitive to all or most of the naturally emerging mutations in the protein. We have recently demonstrated this concept by subjecting a pool of S protein‐binding DNA aptamers for one‐round parallel‐SELEX experiments targeting 5 different S protein variants for binding‐based sequence enrichment, followed by bioinformatic analysis of the enriched pools. This effort has led to the identification of a universal aptamer that recognizes 8 different variants of the spike protein with equally excellent affinity. Abstract : The spike (S) protein of SARS‐CoV‐2 is constantly mutating, producing variants of concerns (VoCs) that can significantly weaken the binding by aptamers engineered to recognize the S protein of the wildtype virus or a specific VoC. We have developed a universal aptamer to solve this problem, which has been shown to recognize 8 different versions of the S protein with equally excellent affinity.